Research on cow traction in Africa: Some lessons to be learned - Jabbar, M.A. (1993)
In sub-Saharan Africa, animal traction is well developed in the Ethiopian highlands and common in the highlands of Kenya and Madagascar, but it is abscent in other highland areas. The technique is also well develop in areas of the semi-arid tropics and is emerging in some parts of the subhumid zone of West Africa. This paper reviews ILCA's research objective and strategy in the light of the experiences of cow traction technology development in southeast Asia. In the Ethiopian highlands, ILCA has tried to introduce two innovations: the single-ox plough and cow traction. It has been reported that oxen used singly are able to cultivate approximately 70 percent of the land that paired oxen can normally prepare. In order to make both single-ox ploughs and cow traction feasible, feed constraints would have to be overcome. ILCA's highland programme is currently investigating the effect of drought, including nutritional and environmental stresses on the physiology of drought oxen and cows. The main objective of this research is to ensure that feed energy is transformed into work energy as efficiently as possible and to help engineers develop appropriate implement prototypes.